(3fWGb GdMeGjI GdLfGFjI ddCWaGd (B:s (3OQGSI ebGQfI (B/s - (3GdeMdGhj, CfjS MSjH GdSjOs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2016)
(3jJfGhd cJGH (B((3fWGb GdMeGjI GdLfGFjI ddCWaGd(B) (3GdPj bGe HJCdjag CfjS MSjH GdeMdGhj aj MhGdj (B(469) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3Mbhb GdCWaGd(B) (3eJVefG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdJegjOj (B: (3eGgjI hQYGjI GdCWaGd, GdHGH GdChd (B: (3GdaUd GdChd (B: (3MeGjI GdWad hQYGjJg hefY GdGYJOGA Ydjg, GdaUd GdKGfj (B: (3JLQje NWa GdCWaGd hENaGA fSHge, GdaUd GdKGdK (B: (3JLQje JYQjV GdCWaGd ddNWQ, GdaUd GdQGHY (B: (3JLQje GSJYeGd GdYfa VO GdCWaGd, GdaUd GdNGeS (B: (3JLQje GdGeJfGY Yf JfajP Mce GdfabI hGdQVGYI hGdMVGfI, GdHGH GdKGfj (B: (3GdaUd GdChd (B: (3JLQje GZJUGH hgJc YQV GdCWaGd, GdaUd GdKGfj (B: (3JLQje JMQjV GdCWaGd Ydi GdaLhQ Ch GdOYGQI, GdaUd GdKGdK (B: (3JLQje JMQjV GdCWaGd hGSJNOGege aj GdJShd, GdaUd GdQGHY (B: (3JLQje JYQjV GdCWaGd ddGfMQGa, GdHGH GdKGdK (B: (3MeGjI hQYGjI GdCeheI (B: (3GdaUd GdChd (B: (3GdQYGjI GdUMjI ddCeheI hGdWad, GdaUd GdKGfj (B: (3GdQYGjI GdJYdjejI ddWad, GdaUd GdKGdK (B: (3QYGjI GdWad GdYGed, GdHGH GdQGHY (B: (3VhGHW GdMeGjI GdLfGFjI ddCWaGd, GdaUd GdChd (B: (3GdCgdjI GdLfGFjI heQGMdgG, GdaUd GdKGfj (B: (3VhGHW GdMeGjI aj ELQGAGJ GdeMGceI, jJVef eQGLY HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B435-457.s
Keywords: (3GdCWaGds -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3eUQs; (3Mbhb GdCWaGds -- (3bhGfjf hJTQjYGJs -- (3eUQs